2016
DOI: 10.1177/0885066616648265
|View full text |Cite
|
Sign up to set email alerts
|

In-Hospital Management and Follow-Up Treatment of Venous Thromboembolism: Focus on New and Emerging Treatments

Abstract: Venous thromboembolism (VTE), encompassing pulmonary embolism (PE) and deep venous thrombosis (DVT), is a major cause of morbidity and mortality of particular relevance for intensivists and hospitalists. Acute VTE is usually managed with parenteral unfractionated heparin or low-molecular-weight heparin, followed by an oral vitamin K antagonist. Data are lacking for optimal treatment of less common occurrences, such as upper extremity DVT, and for approaches such as thrombolysis for PE associated with early sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…The development of new oral anticoagulants (NOACs) offers hope for more therapeutic anticoagulation options in DVT. The safety and efficacy profiles of these new agents, as compared with conventional anticoagulation therapy, are of paramount importance [20,21]. NOACs have a more predictable anticoagulant effect and were recently demonstrated to be as safe as warfarin, although they were administered in fixed doses without routine laboratory monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…The development of new oral anticoagulants (NOACs) offers hope for more therapeutic anticoagulation options in DVT. The safety and efficacy profiles of these new agents, as compared with conventional anticoagulation therapy, are of paramount importance [20,21]. NOACs have a more predictable anticoagulant effect and were recently demonstrated to be as safe as warfarin, although they were administered in fixed doses without routine laboratory monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…22 A standard course of anticoagulation is 3 months for a first provoked LEDVT or at least 6 to 12 months for an unprovoked LEDVT, and this course is typical for UEDVT, although there are no separate guidelines. 21,23 The use of prophylactic anticoagulation is not routinely recommended to prevent UEDVT in patients with central catheters. 6,22,23 However, a randomized phase III trial of 420 patients found a significant reduction in catheter-related DVT, without a significant increase in adverse events, in cancer patients treated with low-dose LMWH or low-dose warfarin as prophylaxis.…”
Section: Anticoagulationmentioning
confidence: 99%
“…21,23 The use of prophylactic anticoagulation is not routinely recommended to prevent UEDVT in patients with central catheters. 6,22,23 However, a randomized phase III trial of 420 patients found a significant reduction in catheter-related DVT, without a significant increase in adverse events, in cancer patients treated with low-dose LMWH or low-dose warfarin as prophylaxis. 24 The differences in the rates of catheter-associated DVT among the control (14.8%), warfarin (6%), and LMWH groups (10%) were statistically significant.…”
Section: Anticoagulationmentioning
confidence: 99%
“…Venous thromboembolism (DVT and/or PE) has an incidence of 1.4 to 2.2 per 1000 persons鈥恲ear among US citizens aged over 45 years, and mortality rate is approximately 25% in the first 30 days. () To prevent PE, DVT patients are usually treated with anticoagulant drugs . However, in patients who have contraindications or are unresponsive to anticoagulation therapy the placement of a filter into the inferior vena cava (IVC) is indicated.…”
Section: Introductionmentioning
confidence: 99%
“…However, in patients who have contraindications or are unresponsive to anticoagulation therapy the placement of a filter into the inferior vena cava (IVC) is indicated. () These filters are devices specifically designed to capture blood clots that are transported by the blood flow within the vein. They are made of titanium or metal alloys, and they are available in a good variety of models.…”
Section: Introductionmentioning
confidence: 99%